Emotional Intelligence contributes to higher education- Lecturer - The Borneo Post (The Borneo Post, 2016)
Dr Muhamad Sophian, Department of Counselling at Faculty of Cognitive Sciences & Human Development, UNIMAS is speaking on EI at International ProCoun'16